The Effect of Extensive Reading on Iranian EFL Learners’ Lexical Bundle Performance: a comparative study of adaptive and authentic texts - Ayatollah Razmjoo; Zahra Montasseri (Journal of English Language Teaching and Learning, 2018)
Formulaic language and sequence as the core characteristic of real-life language and native-like fluency, has been a subject of inquiry in recent decades. The aim of the present study is to investigate the effects of two extensive reading text types, i.e., adaptive and authentic, on Iranian EFL learners’ development of lexical bundles. To this aim, 20 intermediate EFL learners were chosen to participate in a time-series experiment, in which one class received adaptive texts as their extensive reading project, while the other experienced authentic texts of graded readers. The learners were required to read texts and write summaries, out of which the frequency and percentage of lexical bundles were extracted. The results of frequency and t-tests revealed that learners who benefited from adaptive texts were more successful in lexical bundles progress. While the other group also indicated to have improved in terms of multi-word chunks, the shift was not statistically significant. It is recommended that teachers allocate more class time to explicit and implicit instruction of lexical bundles.